2022
DOI: 10.1128/mra.00157-22
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Trichomonas tenax Strain Hs-4:NIH

Abstract: Trichomonas tenax is a flagellated parasite that plays an important role in periodontal disease, with high prevalence worldwide. Its pathogenesis remains largely unknown, and there is very little information on its genome. Here, we present the whole-genome shotgun sequence of T. tenax strain Hs-4:NIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“… * Benabdelkader et al ( 2019 ) and Yang et al ( 2022 ). ** BUSCO score based on the integrated annotations (20,287 proteins) from the 2019 and 2022 draft genomes.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“… * Benabdelkader et al ( 2019 ) and Yang et al ( 2022 ). ** BUSCO score based on the integrated annotations (20,287 proteins) from the 2019 and 2022 draft genomes.…”
Section: Resultsmentioning
confidence: 98%
“…GenSAS (Humann et al, 2019 ) was used to annotate the two draft genome sequences of T. tenax strain Hs-4:NIH (NCBI Genome assemblies PRJEB22701 and ASM2309173v1) (Benabdelkader et al, 2019 ; Yang et al, 2022 ). Identification and masking of repeats was achieved using RepeatMasker (Nishimura, 2000 ) and RepeatModeler (Smit and Hubley, 2008 ) on GenSAS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The area of exosome studies has shown great potential in finding the pathogenicity of various eukaryotic cells. With this new area of proteomics and the recent publication of the T. tenax draft genome [ 93 ], we can possibly move closer to mapping the pathway of T. tenax and developing a possible drug therapy that can control and prevent the transmission of this oral flagellate.…”
Section: Discussionmentioning
confidence: 99%